Assessing discrepancies in heat demand: A case study of diverse energy management systems within the energy performance certificate framework in a student's dormitory - Kaczmarczyk, Michał; Książek, Roger; Hałaj, Elżbieta; Gdowska, Katarzyna; Kapłan, Radosław; Pełka, Grzegorz; Luboń, Wojciech (Energy and buildings, 2025)
This study compares energy certification with actual energy consumption in a university residence, focusing on two control systems: a conventional system with thermostatic heads and an automated system. Aiming to promote effective energy management in public buildings, the research encourages energy-saving behaviors. Conducted at the AGH University Campus in Poland, the study evaluates the heating system control of a residential building. Energy performance calculations were carried out under Polish standards. The measured consumption (97.09 kWh/m2/year) is 188% higher than the certificate value and 258% higher than the Sinum riser. The findings highlight the discrepancy between certification and real-world performance, particularly for automated systems, which are increasingly common but often overlooked in certification processes. This research emphasizes the importance of effective heating management, supporting sustainable building practices, and providing valuable insights for improving energy efficiency and housing management.